Management of Biliary Atresia: A Review - Nahid, Khan Lamia; Rokonuzzaman, Md; Karim, ASM Bazlul; Fatema, Kaniz; Sultana, Azmeri (Bangladesh Journal of Child Health, 2016)
Biliary atresia (BA) is a rare neonatal disease of unknown etiology, where obstruction of the biliary tree causes severe cholestasis, leading to biliary cirrhosis and death in the first years of life, if the condition is left untreated. It is the most common cause of neonatal cholestasis and most common indication for liver transplantation in children. Biliary Atresia clinically presents with jaundice, pale stool, dark urine and hepatomegaly. The treatment of biliary atresia is surgical and is recommended as a sequence of, eventually, two interventions. During the first months of life a hepatoportoenterostomy (Kasai operation) should be performed, in order to restore the biliary flow to the intestine and lessen further damage to the liver. If this fails and/ or the disease progresses towards biliary cirrhosis and life-threatening complications, then liver transplantation is indicated. Age at surgery had a progressive and sustained deleterious effect on the results of the Kasai operation until adolescence. So early detection of biliary atresia is necessary for optimum management and overall survival of the patient. Bangladesh J Child Health 2015; VOL 39 (1) :38-45